SOLO MUSIC DENGAN PENERAPAN SISTEM AKUSTIK - Daniel Yanuar Aditya Beny Prabowo; Suparno Suparno; Amin Sumadyo (ARSITEKTURA, 2015)
Solo’s music world is not yet well accousticly contained because Solo does not have any buliding that specifically used for musical activities. The purpose of this design is to create a container of music activities with a good accoustic quality. The problem that emerge is how to design a building to contain music activities with a good accoustic quality. The planned building apply an accoustical system which able to accomodate every music genre with amplified sound. The accoustic room uses many sound absorber for amplified music. The result is music performance building design, music school design, recording studio design, and music studio design with a good accoustic quality.Keywords: Music Performance Building, Music School, Recording Studio, Music Studio, Accoustic System